Two Birds with One Stone: Technology Adoption and Market Participation through Protection against Crop Failure - Wouter Zant (Tinbergen Institute, 2022)
Most sub-Sahara African agriculture is rainfed and the key production risk is crop failure due to drought or insufficient rains. Major strategies for households to protect against the risk of crop failure are livestock rearing and storage of home produced food. Next to drought, SSA agriculture is characterized by low productivity and limited market participation, issues commonly addressed by promoting use of fertilizer and high-yielding varieties, and cultivation of high-return crops. For several reasons it is likely that protection against crop failure supports adoption of technology and cultivation of high-return crops. Against this background we explore empirically the relationship between technology adoption and market participation on the one hand and start-of-season stocks of staple food and livestock on the other hand, on the basis of 3 rounds of LSMS-ISA household survey data for Malawi (IHS-3, 4 and 5), and a panel version of these data (IHPS). We find statistically significant positive coefficients of maize stocks and livestock on technology adoption and market participation. Data and estimations support a model of developing country agriculture with seasonality, shocks and savings. In terms of policy the results suggest that supporting livestock rearing and food storage at the household level increases labour productivity in agriculture.
Keywords: O13; O16; O33; Q12; Q16; 330; risk; savings; technology adoption; market participation; sub-Sahara Africa